KONTRIBUSI KELINCAHAN DAN KELENTUKAN TERHADAP KEMAMPUAN PASSING BAWAH DALAM PERMAINAN BOLA VOLI PESERTA KELAS XI MAN 2 OGAN KOMERING ILIR - Dimas Andika; Surisman; M. Fajril Rifaldo; Lungit Wicaksono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the contribution of agility and flexibility to the ability of underhand passing in volleyball among eleventh-grade students of MAN 2 Ogan Komering Ilir. The research method used was a correlational method. The research sample consisted of 50 students. The research instruments used were agility, flexibility, and underhand passing tests. The research hypotheses were: (1) there is a contribution of agility to underhand passing ability, (2) there is a contribution of flexibility to underhand passing ability, and (3) there is a contribution of agility and flexibility simultaneously to underhand passing ability. The results of the study showed that: (1) there was a significant relationship between agility and underhand passing ability (r calculated = 0.499 > r table = 0.088), (2) there was a significant relationship between flexibility and underhand passing ability (r calculated = 0.681 > r table = 0.088), and (3) simultaneously, agility and flexibility had a significant relationship with underhand passing ability (r calculated = 0.716 > r table = 0.088) with a contribution of 51.26%.